Genome-Wide Gene Expression Disturbance by Single A1/C1 Chromosome Substitution in Brassica rapa Restituted From Natural B. napus - Zhu, Bin; Xiang, Yang; Zeng, Pan; Cai, Bowei; Huang, Xiaolong; Ge, Xianhong; Weng, Qingbei; Li, Zaiyun (Frontiers in Plant Science, 2018)
Alien chromosome substitution lines are treated as vital germplasms for breeding and genetic mapping. Previously, a whole set of nine Brassica rapa-oleracea monosonic alien addition lines (MAALs, C1-C9) was established in the background of natural B. napus genotype “Oro”, after the restituted B. rapa (RBR) for Oro was realized. Herein, a monosomic substitution line with one alien C1 chromosome (Cs1) in the RBR complement was selected in the progenies of MAAL C1 and RBR, by the PCR amplification of specific gene markers and fluorescence in situ hybridization. Cs1 exhibited the whole plant morphology similar to RBR except for the defective stamens without fertile pollen grains, but it produced some seeds and progeny plants carrying the C1 chromosome at high rate besides those without the alien chromosome after pollination pollinated by RBR. The viability of the substitution and its progeny for the restituted B. rapa diploid further elucidated the functional compensation between the chromosome pairs with high homoeology. To reveal the impact of such aneuploidy on genome-wide gene expression, the transcriptomes of MAAL C1, Cs1 and euploid RBR were analyzed. Compared to RBR, Cs1 had sharply reduced gene expression level across chromosome A1, demonstrating the loss of one copy of A1 chromosome. Both additional chromosome C1 in MAAL and substitutional chromosome C1 in Cs1 caused not only cis-effect but also prevalent trans-effect differentially expressed genes. A dominant gene dosage effects prevailed among low expressed genes across chromosome A1 in Cs1, and moreover, dosage effects for some genes potentially contributed to the phenotype deviations. Our results provided novel insights into the transcriptomic perturbation and gene dosage effects on phenotype in chromosome substitution related to one naturally evolved allopolyploid.